National Survey regarding the Importance of Leadership in PGY1 Pharmacy Practice Residency Training. Issue 11 (December 2015) - Cho, Jonathan C.; Girnys, Jonathan P.
Background: Leadership is considered a professional obligation for all pharmacists. It is important to integrate leadership training in residency programs to meet the leadership needs and requirements of the profession. Objective: To evaluate the importance of leadership development during postgraduate year 1 (PGY1) pharmacy practice residency training as perceived by new practitioners. Methods: A 15-question online survey was distributed to residency-trained new practitioners to assess (1) amount of time dedicated to leadership training during residency training, (2) different leadership tools utilized, (3) residents' participation in various committees or councils, (4) perceived benefit of increased leadership training, (5) importance of having a mentor, (6) understanding of the residency organization's strategic objectives, (7) discussion of Pharmacy Practice Model Initiative (PPMI) during residency training, and (8) adequacy of leadership training in preparation to become a pharmacy practice leader. Results: Although the majority of resident respondents had less than 20% of their residency devoted to leadership, nearly all survey participants acknowledged that leadership is an important component of PGY1 residency training. Residents agreed that their residency experience would have benefited from increased leadership opportunities. Most residents were knowledgeable about their organization's strategic objectives but did not have a full understanding of pharmacy initiatives such as the PPMI. Conclusion: Feedback from residents indicates that an optimal dedication to leadership training would range between 20% and 30% of the residency year. Increased focus on PPMI, mentorship, and expanded use of leadership tools can serve as a way to help meet the future leadership needs of the pharmacy profession and help to better prepare residents to become pharmacy practice leaders.